Luminescent zero-dimensional organic metal halide hybrids with near-unity quantum efficiency. Issue 3 (29th November 2017) - Zhou, Chenkun; Lin, Haoran; Tian, Yu; Yuan, Zhao; Clark, Ronald; Chen, Banghao; van de Burgt, Lambertus J.; Wang, Jamie C.; Zhou, Yan; Hanson, Kenneth; Meisner, Quinton J.; Neu, Jennifer; et al.
Abstract : Single crystalline zero-dimensional organic metal halide hybrids have been developed. Abstract : Single crystalline zero-dimensional (0D) organic–inorganic hybrid materials with perfect host–guest structures have been developed as a new generation of highly efficient light emitters. Here we report a series of lead-free organic metal halide hybrids with a 0D structure, (C4 N2 H14 X)4 SnX6 (X = Br, I) and (C9 NH20 )2 SbX5 (X = Cl), in which the individual metal halide octahedra (SnX6 4− ) and quadrangular pyramids (SbX5 2− ) are completely isolated from each other and surrounded by the organic ligands C4 N2 H14 X + and C9 NH20 +, respectively. The isolation of the photoactive metal halide species by the wide band gap organic ligands leads to no interaction or electronic band formation between the metal halide species, allowing the bulk materials to exhibit the intrinsic properties of the individual metal halide species. These 0D organic metal halide hybrids can also be considered as perfect host–guest systems, with the metal halide species periodically doped in the wide band gap matrix. Highly luminescent, strongly Stokes shifted broadband emissions with photoluminescence quantum efficiencies (PLQEs) of close to unity were realized, as a result of excited state structural reorganization of the individual metal halide species. Our discovery of highly luminescent single crystalline 0D organic–inorganic hybrid materials as perfect host–guest systems opens up a new paradigm in functional materials design.